Application of the Project Method in Efforts to Improve Early Childhood Social Development - Rima Agustiana; Daniel J. Castner; Chulintipa Nopakhun (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this research is to improve social development at an early age through the application of the project method in Kindergarten. Methodology: The methodology used was classroom action research with three cycles, involving 15 group B kindergarten children as research subjects. The research procedure follows the Suharsimi Arikunto model which consists of planning, implementing, observing, and reflecting. The data collected was analyzed using quantitative data analysis techniques and expressed as a percentage. Main Findings: The main finding of this study is that the application of the project method can improve children's social development. Through project activities, children can be involved in socialization and collaboration activities with peers. The project method helps develop social skills and cooperative skills in children. A curriculum that pays attention to activities and experiences that involve cooperation, effort coordination, and conflict resolution among children can provide satisfactory results for their social development. Novelty/Originality of this study: This research contributes to new knowledge about the use of project methods in enhancing early childhood social development. In the context of early childhood education, the project method can be an effective approach to facilitating a child's social development. This research also shows the importance of a learning environment that supports children's social development and the role of educators in monitoring and providing guidance that is beneficial to their environment.